Capturing Candid Moments using Daily Device without Dedicated Human Resource - Yan Sen Paulus; Oscar Karnalim (Universitas Darussalam Gontor, 2018)
In most organizations, candid moments on held events should be captured as images for administrative purposes. For instance, if an event is sponsored by third parties, it is necessary to send some images capturing moments on that event to them. However, human resources are required to capture such images, resulting additional operational cost. This paper proposes a method to capture candid moments without human intervention. Unique to this method, daily device (i.e., mobile phone) is used to replace human resource with the help of a phone holder and a dedicated mobile application. Prior capturing images, given mobile application should be installed to the mobile phone and such phone should be attached to the phone holder that is aimed at event area. Candid images can be then automatically collected by running installed mobile application. According to our evaluation, such method can replace human resource for capturing candid moments using daily device. Further, it is more efficient than video recording (i.e., an alternative to capture candid moments) in terms of used battery power and memory.